The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1997
DOI: 10.1136/bjo.81.11.980
|View full text |Cite
|
Sign up to set email alerts
|

Clinical experiences of infectious scleral ulceration: a complication of pterygium operation

Abstract: Aims-To report the special clinical manifestations and determine the appropriate management of infectious scleral ulceration. Methods-A retrospective study was performed on 30 eyes with infectious scleral ulceration. Information was recorded on patients' age, onset and course of disease, pathogenic organism, clinical presentations, methods of diagnosis, treatment, and outcome. Results-10 cases (33.3%) were accompanied by corneal involvement. Subconjunctival abscess was noted in 16 cases (53.3%). 17 cases (56.7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
94
4

Year Published

2002
2002
2019
2019

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 82 publications
(103 citation statements)
references
References 28 publications
5
94
4
Order By: Relevance
“…Huang et al reported 16 cases of infective scleritis, of which three were fungal (18%). Lin et al 6 reported 30 patients of infectious scleritis of which only one had fungal keratitis (3%). In a series by Hsio et al, 7 only one case had fungal etiology (5%) out of Clinical experiences of infectious scleritis from a developing country V Jain et al…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Huang et al reported 16 cases of infective scleritis, of which three were fungal (18%). Lin et al 6 reported 30 patients of infectious scleritis of which only one had fungal keratitis (3%). In a series by Hsio et al, 7 only one case had fungal etiology (5%) out of Clinical experiences of infectious scleritis from a developing country V Jain et al…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6][7][8] Fungal scleritis was a rare entity. Huang et al reported 16 cases of infective scleritis, of which three were fungal (18%).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations